Melaleuca alternifolia Cheel (Myrtaceae), Citrus limon (L.) Burm.f. (Rutaceae), Caryocar brasiliense Cambess (Caryocaraceae), Pelargonium graveolens L´Hér (Geraniaceae) and Propolis extract as in vitro Sporothrix schenckii inhibitors - Garcia, Sabrina Rosa Magalhães (2023)
Sporotrichosis, a mycosis caused by fungus of the genus Sporothrix, has the itraconazole therapy of first choice. Resistance reports have been observed to both Itraconazol and amphotericin B, culminating in treatment failures and clinical cases like pulmonary or systemic infections. The aim of this study was to evaluate in vitro the effect of essential oils from Melaleuca alternifolia Cheel (Myrtaceae), Citrus limon (L.) Burm.f. (Rutaceae), Caryocar brasiliense Cambess (Caryocaraceae), Pelargonium graveolens L´Hér (Geraniaceae) and pure propolis extract or associated in inhibiting of S. schenckii growth. The methods used were Kirb-Bauer, disk diffusion on agar, Minimum Inhibitory Concentration and Minimum Fungicide Concentration. The essential oils and the propolis extract were effective in inhibiting fungal growth, overcoming the effects of itraconazole. Itraconazole was able to inhibit the growth of S. schenckii up to a dilution of 4mg.mL-1 (10-3 dilution). The essential oils of melaleuca, geranium, lemon, all at a concentration of 10mg.mL-1 and propolis extract at a concentration of 20mg.mL-1, were able to inhibit, respectively, the development of this fungus at concentrations lower than 0.325mg.mL-1 (10-6 dilution), 0.15625mg.mL-1 (10-7 dilution), 0.325mg.mL-1 (10-4 dilution) and 0.625mg.mL-1 (10-6 dilution). Geranium and melaleuca essential oils showed the best inhibition and fungicidal potential against S. schenckii. These results suggest the importance of in vivo tests to evaluate the use of these herbal medicines as an alternative treatment against sporotrichosis.